Germinations 9.European projects for young artists. ([S.l.] : [s.n.])
Arachovitis, Lambros ; Barba, Dimitra ; Boelens, Peter ; Meyers, Koen ; Bosch, Susanne ; Bourgin, Frédéric ; Cazin, Marie-Laure ; Charissis, Christos ; Chilf, Mária ; Eliasson, Olafur ; Commeleran, Oriol Font ; Fontalba, Txaro ; Frieling, Gijs ; Gillen, Tina ; Heijne, Mathilde ter ; Hijosa, Gemma Micaela Garcia ; Hyllemose, Ellen Gry ; Kenny, Stephen ; Korbicka, Pavel ; Koza, Janek ; Kroth, Doris ; Lang, Burkhard ; Lange, Astrid ; Leblanc, Céline ; Levinthal, Nina ; Liaudet, David ; Luciano, Caterina ; Lüsing, Frank ; Madácsy, István ; Matesanz, Chelo ; Metzger, Michaela ; Mijares ; Moulin, Nicolas ; Mréjen, Valérie ; Muniategi-Andikoetxea, Manu ; Neidhard, Simone Eva ; O'Neill, Paul ; Petö, Hunor ; Ploug, Anne Marie ; Podsladly, Dominik ; Poehl, Charlotte von ; Rello, Maria Jesús ; Sammartano, Antonio ; van Schaijk, Mieke ; Sedlácková, Sarka ; Boggio Sella, Marco ; Stage, Judith ; Sztwiertnia, Grzegorz ; Terlinden, Jens ; Thoss, Silke ; Trzebinski, Piotr ; Valentinetti, Roberta ; Villanueva, Alicia Martin ; Vogl, Filemon ; Volquardsen, Fiona ; Vounatsou, Myrto ; Weil, Alejandra
boek